Erythrocyte filterability in normal and high-risk pregnancy - Rodgers, B D; Hreshchyshyn, M M; Lee, R V; Rodgers, D; Ambrus, C M (Obstetrics and gynecology (New York. 1953), 1988)
Erythrocyte filterability was studied longitudinally in normal pregnancy and in certain categories of high-risk pregnancy. Study subjects included ten normal controls, 12 insulin-dependent diabetics, eight gestational diabetics, and five essential hypertensives. Our results indicate that erythrocyte filterability remains relatively stable over the course of normal gestation. We noted no differences between controls and essential hypertensives or gestational diabetics, although a favorable effect of insulin therapy was suggested in gestational diabetics. Erythrocyte filterability and mean arterial blood pressure were not related. Insulin-dependent diabetics demonstrated a significantly elevated and widely varying erythrocyte filterability, and individual patient trends correlated well with outcome. Fibrinogen levels in diabetics rose precipitously and were significantly higher than normal throughout gestation. Fibrinogen levels paralleled changes in erythrocyte filterability, with the two parameters positively correlated. Mean glucose control had no influence on filterability. We conclude that in the diabetic pregnancy, varying erythrocyte filterability is related to altered fibrinogen metabolism and may contribute to perinatal morbidity.